Culture shock and adaptation strategies of Indonesian migrant workers in the Japanese agriculture field - Nunuk Endah Srimulyani; Lim, Beatrice Fui Yee (Common Ground Research Networks, 2024)
Japan’s agricultural industry is facing a major labor shortage due to aging demographics and a declining population. This study examines the challenges that Indonesian migrant workers encounter while working in Japan’s agricultural sector, as well as their adaptation strategies and competitiveness. As Indonesian migrant workers come from non-Kanji origin countries, it is assumed that language is a major barrier for them. Additionally, as a predominantly Muslim country, religious practices such as praying five times a day and fasting during Ramadan may hinder their competitiveness as migrant workers in Japan. This qualitative research project successfully identified and analyzed the adaptation strategies adopted by Indonesian workers. Data were collected online using Google forms, with seventeen respondents from Chiba, Ibaraki, Gifu, and Gunma Prefecture, who worked in cattle breeding and agriculture. The survey and interviews revealed that workers from Indonesia face significant challenges in Japanese language proficiency, differences in work culture, and extreme weather conditions, especially in snowy areas like Gunma. To address these issues, the workers implemented various behavioral and process adaptation strategies, which included addressing differences in habits, work culture, language, environment, and religious matters. The study found that maintaining strong family ties within the company was an effective strategy for overcoming these challenges. This fosters strong social bonds, benefits both parties, and makes it easier for employers to retain workers, from apprentices to skilled workers.